The virtues of the vicious : Jacob Riis, Stephen Crane, and the spectacle of the slum - Gandal, Keith (Oxford University Press on-line., 1997)
In this study, the author demonstrates how, in the last decade of the 19th century, the slum became a source of spectacle as never before - in newspapers, photographs and literature. With close readings of texts by Crane and Riis, he argues that this amounted to a revolution of ethics.